2018
DOI: 10.1111/jon.12588
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Mild Cognitive Impairment May be Stratified by Advanced Diffusion Metrics and Neurocognitive Testing

Abstract: BACKGROUND AND PURPOSE Mild cognitive impairment (MCI) is a prevalent disorder, with a subset of patients progressing to dementia each year. Although MCI may be subdivided into amnestic or vascular types as well as into single or multiple cognitive domain involvement, most prior studies using advanced diffusion imaging have not accounted for these categories. The purpose of the current study was to determine if the pattern of diffusion tensor imaging (DTI) and diffusion kurtosis imaging (DKI) metrics in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In addition, increased values for MD, AD, and RD and decreased FA, MK, AK, and RK were observed in the corpus callosum, bilateral cingulate bundle, bilateral temporal and frontal regions of patients with early AD [20]. According to a previous study, the FA and MK values of DKI are usually reduced due to microstructure damage to the cingulate cortex [8]. [21].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, increased values for MD, AD, and RD and decreased FA, MK, AK, and RK were observed in the corpus callosum, bilateral cingulate bundle, bilateral temporal and frontal regions of patients with early AD [20]. According to a previous study, the FA and MK values of DKI are usually reduced due to microstructure damage to the cingulate cortex [8]. [21].…”
Section: Discussionmentioning
confidence: 80%
“…In previous studies, microstructural changes in patients with MCI have been observed using diffusion tensor imaging (DTI). Two of the most widely reported DTI metrics, fractional anisotropy (FA) and mean diffusion (MD), are altered in multiple white matter tracts of patients with MCI [8,9]. Diffusion kurtosis imaging (DKI) extends conventional DTI measures by detecting microstructural changes not only in white matter (WM, anisotropic tissues) but also in gray matter (GM, isotropic tissues) because it is independent of the spatial direction of the structures [10].…”
Section: Introductionmentioning
confidence: 99%
“…At present, we have not found any articles specifically discussing the relationship between DKI and CI in CAD patients. However, a study on a population with pure cognitive impairment found that DKI metrics were closely related to cognitive function scores in regions such as the posterior limb of the internal capsule ( Allen et al, 2019 ). This finding is consistent with our research results.…”
Section: Discussionmentioning
confidence: 99%
“…When the integrity of white matter fibers is damaged, the dispersion barrier is damaged, resulting in weakening of the dispersion ability of water molecules along the direction of white matter fiber bundles, together with enhancement of the dispersion ability to the periphery, and consequently, FA value is decreased. Many studies have also shown that the FA value of the hippocampus is generally reduced in patients with mild cognitive impairment ( Zhao et al, 2014 ; Allen et al, 2019 ). The fornix is composed of output fibers of the hippocampus and is an important structure that maintains its normal function.…”
Section: Discussionmentioning
confidence: 99%